The Potential of Gelam (Melaleuca leucadendra) Bark Extract as an Antibacterial Agent Against Pseudomonas aeruginosa and Enterococcus faecalis - Yusro, Fathul; Mariani, Yeni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study aims to evaluate the antibacterial activity of Melaleuca leucadendra (Gelam) bark extract against Pseudomonas aeruginosa and Enterococcus faecalis. Bark samples were collected from Karimunting Village, Bengkayang Regency, and extracted using maceration with 96% ethanol. Antibacterial testing was conducted using the disc diffusion method on MHA (Mueller Hinton Agar), with bacterial suspensions adjusted to McFarland standard 1. The results showed that the extract exhibited concentration-dependent antibacterial activity. The highest inhibition zones were observed at a concentration of 200 mg/mL, measuring 4.5 mm for P. aeruginosa and 3.5 mm for E. faecalis. Although the inhibitory effect was relatively low compared to the positive control (amoksilin), these findings indicate the potential of Gelam bark extract as a natural antibacterial agent. Further studies are recommended to isolate active compounds, assess toxicity, and develop formulations to enhance its antibacterial efficacy.